Transforaminal Epidural Steroid Injection Improves Neuropathic Pain in Lumbar Radiculopathy: A Prospective, Clinical Study - GÜNDÜZ, OSMAN HAKAN (Wolters Kluwer Medknow Publications, 2021)
Objective: This study aims to evaluate the effects of transforaminal epidural steroid injection (TFESI) on neuropathic pain (NP) in patients with chronic unilateral radiculopathy due to lumbar disc herniation (LDH). Patients and Methods: Between September 2018 and April 2019, a total of 61 patients who were diagnosed with unilateral/unilevel radiculopathy due to LDH and were scheduled for single-level TFESI were included in this study. The Numeric Rating Scale (NRS), modified Oswestry Disability Index (ODI), Beck Depression Inventory (BDI), and NP-Douleur Neuropathique 4 Questionnaire (DN4) were used before the procedure and at 1 hour, 3 weeks, and 3 months after the procedure. Results: There was a significant decrease in the NRS and significant improvement in the ODI, BDI, and DN4 scores in all patients at all postprocedural timepoints (P < 0.05). The number of patients with NP decreased from 35 (60.3%) at baseline to 23 (41.2%) at 3 months (P = 0.001). The NRS scores were similar at 3 weeks and 3 months between the patients with and without NP (P > 0.05). The ODI scores were significantly higher at 3 months in the patients with NP than those without NP (P = 0.013). The BDI scores at baseline, 3 weeks, and 3 months were significantly higher in the patients with NP than those without NP (P < 0.001, P = 0.016, and P = 0.016, respectively). Conclusion: Our study results suggest that TFESI is an effective and safe method to decrease not only nociceptive but also NP component in patients with chronic radiculopathy due to LDH. Clinicians should keep in mind that NP is a risk factor that adversely affects the TFESI success and patients should be evaluated before the procedure. © 2021 Wolters Kluwer Medknow Publications. All rights reserved.
Keywords: Epidural injections; herniated disc; neuropathic pain